Aplikasi Ilmu Ādāb al-Baḥth wa al-Munāẓarah dalam Isu Ru’yah Allāh: Application of Adab al-Bahth wa al-Munazarah in the Issue of Ru’yah Allah - SAIFUL, MOHD SAIFUL AQIL NAIM BIN SAFUL AMIN; Syed Mohammad Hilmi Syed Abdul Rahman , (Jurnal Usuluddin, 2022)
The issue of ru’yah Allāh is an issue of belief that has long been a place in the debate stage of scholars across sects and streams since the second century of Hijrah. Among the sects that are the main rivals of the Ahl al-Sunnah wa al-Jamā'ah sect on this issue is al-Mu'tazilah who deny the necessity of ru’yah Allāh either in this world or in the hereafter by using the argument of revelation, reason and language. This issue is very important to pay attention to because it involves an important faith debate. Scholars of Ahl al-Sunnah wa al-Jamā'ah wa al-Jamā'ah such as al-Abū al-Ḥasan al-Ash'arī (d. 323 H), Abū Ḥāmid al-Ghazālī (d. 505 H), Sa' ad al-Dīn al-Taftāzānī (d. 792 H) and Muḥammad al-Sanūsī (d. 895 H) interacted with them in the form of dialectic and debate centered on the methodology of ādāb al-baḥth wa al-munāẓarah science. Therefore, this study was written to examine the application of ādāb al-baḥth knowledge practiced by the scientist in the issue of ru'yah Allāh to identify the significance of this knowledge in arguing and upholding the truth. This study goes through the process of content analysis of scholarly documents in the science of faith to obtain relevant information. The study found that the methods applied have an important role in disentangling the arguments used, unraveling the errors in arguments and proving the truth of a claim related to the issue of ru’yah Allāh thus helping to break arguments that contradict the Quran and the Sunnah.